Gender and well-being around the world: some insights from the economics of happiness - Graham, Carol; Chattopadhyay, Soumya (Chicago, 2012)
"A wide body of research explores gender differences in welfare outcomes, and their implications for economic development. We aim to contribute to this work by looking at differences in reported well-being (happiness) across genders around the world. We examine differences across genders within countries, comparing age, income, education, and urban versus rural cohorts, and explore how those same within country differences vary in countries of different development levels. Our findings, based also on previous research on well-being more generally, highlight some consistent patterns across genders, with women typically happier than men in the world as a whole, with the exception of the poorest sample of countries. We also find substantial differences in the standard relationships between key variables - such as marriage - and happiness when we take differences in gender rights into account. Our research also suggests that cross-gender differences in well-being are affected by the same empirical and methodological factors that drive the paradoxes underlying the income and happiness debates more generally, with norms and expectations playing an important mediating role. Women's happiness seems to fall - at least in the short-term - when there are changes/improvements in gender rights, in keeping with our more general findings on the drops in reported well-being that are often associated with the process of acquiring agency."